Long-term efficacy and safety of antitumour necrosis factor alpha treatment in rhupus: an open-label study of 15 patients. Issue 2 (29th December 2017) - Danion, François; Sparsa, Laetitia; Arnaud, Laurent; Alsaleh, Ghada; Lefebvre, François; Gies, Vincent; Martin, Thierry; Lukas, Cédric; Durckel, Jean; Ardizzone, Marc; Javier, Rose-Marie; Kleinmann, Jean-François; et al.
Abstract : Background: The efficacy of antitumour necrosis factor alpha (anti-TNF-α) treatment is well recognised in rheumatoid arthritis (RA) but remains controversial in systemic lupus erythematosus (SLE). Therefore, the role of anti-TNF-α treatment in 'Rhupus', a disease sharing features of RA and SLE, is still debated. Objective: To evaluate the efficacy and tolerance of anti-TNF-α in patients with rhupus. Methods: Fifteen patients with rhupus with Disease Activity Score 28 (DAS 28) >3.2 despite conventional disease-modifying anti-rheumatic drugs were included in an open-label study. Patients were monitored at months (M) 3, 6, 12, 24 and 60 with SLE Disease Activity Index (SLEDAI) and DAS 28. Statistical analyses were performed using Bayesian methods and Prob >97.5% was considered significant. Results: Twelve patients were treated with etanercept for a median duration of 62.5 (range: 6–112) months and three patients by adalimumab during 36.0 (range: 4–52) months. At baseline, median DAS 28 and SLEDAI were 5.94 (4.83–8.09) and 6 (4–8), respectively. DAS 28 and SLEDAI decreased significantly after 3 months, respectively, to 3.70 (1.80–6.42) and 4 (0–6) (Prob >99.9%, for both). These changes persisted at M6, M12, M24 and M60 (Prob >99.9%, for all). Median prednisone dose decreased significantly from 15 (5–35) mg/day to 5 (0–20) mg/day after 6 months and over the follow-up (Prob >99.9%, for all). Tolerance was acceptable, with a severe infection rate of 3.0 per 100 patient-years. Conclusion: This pilot study suggests that anti-TNF-α is effective in patients with rhupus with refractive arthritis and has an acceptable safety profile.